Hydrodynamic performance of a newly-designed Antarctic krill trawl using numerical simulation and physical modeling methods. (1st May 2019) - Wan, Rong; Jia, Mingxiu; Guan, Qinglong; Huang, Liuyi; Cheng, Hui; Zhao, Fenfang; He, Pingguo; Hu, Fuxiang
Abstract: Antarctic krill ( Euphausia superba ) is one of the most abundant commercial species in the world and still has great potential for further development and utilization. It is, however, very important that the resource is utilized in a sustainable manner in terms of efficiency and selectivity, which can be enhanced through proper design of pelagic trawls that are used for harvesting the species. Pelagic trawls rely heavily on hydrodynamic forces acting on the netting to form desirable shapes. It is thus crucial to understand hydrodynamic forces acting on the trawl to predict its performance. A large Antarctic krill trawl with a net opening circumference of 200 m was designed for a fishing vessel (2855 kW) and analyzed by numerical simulation and physical model tests. A numerical model of Antarctic krill trawl was established based on the finite element method. The principle of minimum potential energy was employed to determine the equilibrium configuration and the tension distribution of the trawl in a uniform current. The Newton–Raphson method was applied to solve the equilibrium equation. A series of physical model tests were conducted in a flume tank to verify the result from numerical simulation. The results showed that the trawl with a net opening circumference of 200 m had superior hydrodynamic performance and could be well matched with fishing vessels of the class for the efficient production of Antarctic krill. This paper demonstrates the use of scientific methods for the design of large Antarctic krill trawls and the application of numerical simulation to study the hydrodynamic performance. Highlights: A new Antarctic krill trawl is designed. Study on hydrodynamic performance of the Antarctic krill trawl. Verifying the accuracy of numerical simulation. Calculation of shape and tension distribution.